Validity and Reliability Study of IST 2000R Indonesian Version - Fadillah Fadillah; Medianta Tarigan (Journal of Educational, Health and Community Psychology, 2022)
In addition to the limited use of the Intelligenz Struktur Test 2000 Revised (IST 2000R), the adaptation process of the IST 2000R into the Indonesian version is thought to influence this test. Therefore, this study aims to conduct a review of the psychometric properties of the IST 2000R Indonesian version. The research method used is quantitative research and 919 participants, aged 17-30 years, M = 380; F=539 were involved as the sample. The data analysis technique used consisted of the construct validity test using Confirmatory Factor Analysis (CFA) and estimation of internal consistency reliability Cronbach Alpha. Analysis showed that fit results after modification indices with a p-value is 0.05675, RMSEA index is 0.023 (<0.05), GFI 0.99, CFI 0.99. and NFI 0.98 (> 0.9). The results of Composite Reliability (CR) on IST 2000R show that the reliability of sub-tests that measure numerical and abstract intelligence is good, while the reliability of verbal sub-test items is low shown by CR is 0.44.